تطبيق نموذج التعلم بالاكتشاف لترقية التفكير النقدي تعليم مهارة القراءة لطلاب الصف العاشر المدرسة الثانوية الاسلامية الحكومية الاولى جومبانج - Nafis Fauzul Hanif; Lailatul Qomariyah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study aims to describe the application of discovery learning model in learning maharah qira'ah, the development of students' critical thinking skills, as well as the supporting and inhibiting factors of its implementation. This research uses a descriptive qualitative approach with observation, interview, and documentation techniques. The results showed that the discovery learning model was applied through group work, with activities to find the meaning of mufrodat, compose sentences, understand the meaning of the text, and conclude the content of the reading. The results of group work were presented and discussed with the teacher. Students' critical thinking skills improved, shown through independence, curiosity, and the ability to understand and communicate the content of the text. Supporting factors include good communication, learning motivation, and adequate facilities, while inhibiting factors include egoism in the group, differences in understanding, and time constraints. This study illustrates that the application of discovery learning can be an effective alternative learning model to increase students' engagement and critical thinking skills in qira'ah learning.